Accessible Filmmakers: Towards a Professional Profile - Fascioli-Álvarez, Florencia (Journal of Audiovisual Translation, 2022)
Although many film professionals have adopted the Accessible Filmmaking (AFM) approach in their work, there is yet no clear professional profile or coherent training. What is an accessible filmmaker? How do they create accessible versions of films? What production, technical, and aesthetic challenges do they face? This article will explore some current AFM practices used by film professionals in Uruguay by means of a qualitative methodology based on fourteen semi-structured interviews with filmmakers and crew members. Results indicate that the film professionals interviewed recognize different degrees of involvement with Media Accessibility, from scant and sporadic engagement to active participation. One major obstacle they face is lack of knowledge on the specifics of accessibility. Although Media Accessibility might at first seem relatively easy to implement, it is in fact challenging to navigate in audiovisual works, all the more so if the tools are organically integrated into a film. On the basis of observation, four skills useful to an accessible filmmaker are described. Lay summary Traditionally, translation and media accessibility are added to films once they have been completed. However, the Accessible Filmmaking (AFM) approach proposes the integration of translation and media accessibility from the early stages of the audiovisual production process, looking for collaboration between the creative team of the film and the experts in charge of translating it. To make an accessible film we need a new professional profile: the accessible filmmaker. As this role is still little explored, this article proposes an approach to the definition of its profile. To do so, it considers the translation and accessibility practices carried out by 14 film professionals interviewed in Uruguay. The study reveals different degrees of involvement with media accessibility from the participants, some with a scarce and occasional commitment, others with an active participation. This involvement is challenged by the lack of knowledge they have on this issue. When the interviewed reflect on how translation and accessibility can be integrated earlier in the film workflow, it seems easy to implement but challenging on how it could add an artistic value to the film.